The Effect of State Budget Ratification and Expenditure on The Indonesian Capital Market : An Empirical Study on The LQ 45 Index Shares - Agus Bandiyono; Priska Amalia (University of Merdeka Malang, 2021)
This study analyzes the market reaction to the State Revenue and Expenditure Budget (APBN) ratification using the event study method. The population in this study were all companies listed on the LQ45 index on the Indonesia Stock Exchange during the period 2009 to 2018, which could reach 101 emissions with a sample of 17 emissions through the purposive sampling technique. The criteria used in selecting the sample were that the stock was consistently in the LQ45 index from 2009 to 2018; the stock was active during the observation period. The share issuer does not take corporate action during the observation period to minimize the confounding effect (confounding effect). The analysis technique uses a paired sample t-test five days before and five days after the ratification of the State Budget (APBN). The results showed that the significant ratification events did not significantly differ in the average abnormal return and the average trading volume activity between before and after the event. There is no significant difference because market players have anticipated the information contained in the ratification event at the initial stage of its preparation. DOI : https://doi.org/10.26905/jkdp.v25i2.5134